Bougie-associated bronchial injury complicated by a nephropleural fistula after percutaneous nephrolithotomy: a tale of two complications. (17th April 2018) - Pande, Aparna; Ramachandran, Rashmi; Rewari, Vimi
Abstract : We present a case of bronchial injury following bougie-assisted endotracheal intubation in a patient with difficult airway scheduled to undergo right percutaneous nephrolithotomy under general anaesthesia. The patient developed pleuritic pain along with right pleural effusion on the third postoperative day which was diagnosed by the anaesthesiologist who was following up the patient for airway trauma-associated complications. However, the patient was diagnosed to have a nephropleural fistula, a rare complication of supracostal access to percutaneous nephrolithotomy, which was managed successfully.